BEHAVIOURAL ECONOMICS : A VERY SHORT INTRODUCTION - MICHELLE BADDELEY (OXFORD UNIVERSITY PRESS UK, 2017)
Behavioural economics blends insights from economics and psychology to explain how people make everyday decisions. Analysing the forces that drive everyone's behaviour, the book helps us understand what people are motivated by, our impulse purchases, why we struggle to save, and how supermarkets can manipulate what and how much we buy.
Keywords: ECONOMICS-PSYCHOLOGICAL ASPECTS